Linking Political TV Shows with Female Lead Characters to Political Engagement: The Roles of Parasocial Processes and Gender Identity. Issue 5 (1st December 2020) - Hoewe, Jennifer; Wiemer, Eric C.; Adekunle, Tiwaladeoluwa; Barton, Rachel; Jett, Janel; Pijanowski, Alexander
ABSTRACT: This study tests the relationship between viewing political TV shows with female lead characters and political engagement. It argues that parasocial processes provide the necessary link and gender identity is a critical moderating variable. Results of an in-lab experiment show that viewing a female lead character in a politically-driven plotline increases political self-efficacy, interest, and participation among individuals who identify as more feminine, and this effect is mediated by parasocial interactions with that character. Coupled with prior research, these results demonstrate that more feminine individuals may become more politically engaged through parasocial interactions and relationships with fictional female political leaders.